Analisis Teknik Penambahan Dan Pengurangan Hasil Terjemahan dalam Acara Televisi National Geographic - Yoharwan Dwi Sudarto (Journal of Social, Culture, and Language, 2023)
This study aims to analyze the technique of subtracting and adding translation results in National Geographic television shows. There are several aspects studied in this technique, namely amplification, compression, generalization, particularization, and reduction. The techniques were proposed by Molina Albir. In translation, subtraction is often done for several reasons. One reason is efficiency. Some words contained in the source language (SL) are not translated into the target language (TL). Likewise with the addition of translation results which are usually added to the target language whose purpose is to provide additional explanation. Keywords: Translation, Amplification, Compression, Generalization, Particularization, Reduction